2017
DOI: 10.3945/ajcn.116.144808
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nutrition training for health care staff on learner and patient outcomes in adults: a systematic review and meta-analysis

Abstract: Background: Nutrition training for health care staff has been prioritized internationally as a key means of tackling malnutrition; however, there is a lack of clear evidence to support its implementation. Systematic reviews in other fields of training for health care staff indicate that training strategies may have a beneficial impact on learner and patient outcomes. Objectives: We assessed whether nutrition training for health care staff caring for nutritionally vulnerable adults resulted in improved learner … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…This is in line with results from a meta-analysis of the evidence of the effect of nutritional knowledge on daily processes and patient outcomes, where it is concluded that it can have severe consequences for the patients when the healthcare professionals’ knowledge or understanding of nutrition are sparse, and it specifically concluded that improvements in the level of knowledge about nutrition had a positive influence on the nutritional related documentation performed by registered nurses. [42]. A significant beneficial effect of increased nutrition knowledge among healthcare workers in nursing homes was found on a range of outcomes, such as increased nutritional intake, improvements in weight and body composition, improvements in reported eating difficulties and finally a significantly lower prevalence of malnutrition in patients [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in line with results from a meta-analysis of the evidence of the effect of nutritional knowledge on daily processes and patient outcomes, where it is concluded that it can have severe consequences for the patients when the healthcare professionals’ knowledge or understanding of nutrition are sparse, and it specifically concluded that improvements in the level of knowledge about nutrition had a positive influence on the nutritional related documentation performed by registered nurses. [42]. A significant beneficial effect of increased nutrition knowledge among healthcare workers in nursing homes was found on a range of outcomes, such as increased nutritional intake, improvements in weight and body composition, improvements in reported eating difficulties and finally a significantly lower prevalence of malnutrition in patients [42].…”
Section: Discussionmentioning
confidence: 99%
“…[42]. A significant beneficial effect of increased nutrition knowledge among healthcare workers in nursing homes was found on a range of outcomes, such as increased nutritional intake, improvements in weight and body composition, improvements in reported eating difficulties and finally a significantly lower prevalence of malnutrition in patients [42]. Increased knowledge and understanding about nutrition and documentation can improve nutritional care practice.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the observation period was too short to accurately reflect this activity for M2 and M3. In the literature on home care services, many researchers have reported the effects of training on specific objectives [17]. Tourangeau et al [18] have also highlighted the importance of training for providing quality client care.…”
Section: Discussionmentioning
confidence: 99%
“…However, systematic review of trials of nutrition training for health care staff conducted by Marples, Baldwin, & Weekes (2017) showed that the use of unvalidated self-administered questionnaires to measure learner and patient outcomes after staff training makes it difficult to draw firm conclusions regarding the results. Thus, this study fills a gap in the literature by providing a validated tool to evaluate the capability of PHC professionals to apply the BDG, internationally recognized by their holistic paradigm of healthy diet (Blake, Durão, Naude, & Bero, 2018;).…”
Section: Discussionmentioning
confidence: 99%
“…, in Brazil, there are findings suggesting a fragmented work process involving nutritionists acting in PHC (Cervato-Mancuso, Tonacio,Silva, & Vieira, 2012;Pedraza & Santos, 2017), although interprofessional collaboration practices are expected.According toKris-Etherton et al (2014), researchers are needed to identify and evaluate new approaches or strategies for educating health care professionals about nutrition and healthy lifestyle behaviors and how interprofessional nutrition education with multidisciplinary teamwork contributes to more coordinated and qualified care.Training for health care staff is recognizably able to produce positive effects on professionals' practice and attitudes(Berggren et al, 2015;Marples et al, 2017;Torres, Amaral, Amorim, Cyrino, & Bodstein, 2010). ForGotwals (2018), effective nutritional health promotion interventions are those that lead to an increased perceived self-efficacy in knowledge and ability to counsel.…”
mentioning
confidence: 99%